2015
DOI: 10.1073/pnas.1413493112
|View full text |Cite
|
Sign up to set email alerts
|

Seminal CD38 is a pivotal regulator for fetomaternal tolerance

Abstract: A successful pregnancy depends on a complex process that establishes fetomaternal tolerance. Seminal plasma is known to induce maternal immune tolerance to paternal alloantigens, but the seminal factors that regulate maternal immunity have yet to be characterized. Here, we show that a soluble form of CD38 (sCD38) released from seminal vesicles to the seminal plasma plays a crucial role in inducing tolerogenic dendritic cells and CD4+ forkhead box P3 + (Foxp3 + ) regulatory T cells (Tregs), thereby enhancing ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 52 publications
0
33
0
9
Order By: Relevance
“…More specifically, a soluble form of CD38 (sCD38) released from seminal vesicles to the seminal plasma might play a role in this process. Soluble CD38 in seminal plasma was shown to be crucial for the induction of uterine tolerogenic dendritic cells (DCs) and CD4+Foxp3+ Tregs . Deficiency of sCD38 in seminal fluid increased the loss rate of allogeneic foetuses, which could be rescued by a direct injection of recombinant sCD38 into the uterus.…”
Section: Tregs In Normal Pregnancymentioning
confidence: 99%
“…More specifically, a soluble form of CD38 (sCD38) released from seminal vesicles to the seminal plasma might play a role in this process. Soluble CD38 in seminal plasma was shown to be crucial for the induction of uterine tolerogenic dendritic cells (DCs) and CD4+Foxp3+ Tregs . Deficiency of sCD38 in seminal fluid increased the loss rate of allogeneic foetuses, which could be rescued by a direct injection of recombinant sCD38 into the uterus.…”
Section: Tregs In Normal Pregnancymentioning
confidence: 99%
“…Thus, unsupervised purely statistical generation of signatures appears more sensitive than supervised methods and may reveal early changes of immune-annotated signatures that could be related to Treg activation by seminal fluid (55). A recent study demonstrated that a soluble form of CD38 released from seminal vesicles induces tolerogenic DCs and activates Tregs, thereby enhancing maternal immune tolerance and protecting the fetus from rejection (56).…”
Section: Discussionmentioning
confidence: 99%
“…Фаллопиевы трубы, в которых происходит оплодотворение, содержат фак-торы, подавляющие активность системы компле-мента -CD46, CD55, CD59 [4] и препятствуют ком-плементопосредованному лизису раннего эмбриона при наличии у матери антител к МНС антигенам от-ца, вызванных иммунизацей в ходе предыдущей бе-ременности. В семенной плазме обнаружены раство-римые факторы, такие как TGF-β и CD38, которые, вероятно, участвуют в подготовке матки к толерант-ности, и при отсутствии которых частота успешных зачатий снижается [5,6].…”
Section: плод как аллотрансплантатunclassified
“…Фаллопиевы трубы, в которых происходит оплодотворение, содержат фак-торы, подавляющие активность системы компле-мента -CD46, CD55, CD59 [4] и препятствуют ком-плементопосредованному лизису раннего эмбриона при наличии у матери антител к МНС антигенам от-ца, вызванных иммунизацей в ходе предыдущей бе-ременности. В семенной плазме обнаружены раство-римые факторы, такие как TGF-β и CD38, которые, вероятно, участвуют в подготовке матки к толерант-ности, и при отсутствии которых частота успешных зачатий снижается [5,6].Преимплантационный эмбрион также не экс-прессирует молекул МНС и, вдобавок, окружен zona pellucida, которая защищает его от гуморальных фак-торов иммунитета, таких как антитела. После при-крепления в матке фертилизационная мембрана рас-творяется, и эмбрион становится чувствительным к иммунной атаке.…”
unclassified